Sirah Nabawiyah dan Demitologisasi Kehidupan Nabi - Ahmad ‘Ubaydi Hasbillah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2012)
There are two aspects in the personality of the Prophet Muhammad: revelation and culture. Both of them developped the character and the behavior of the Prophet Muhammad as a mere human being as well as a prophet. It is difficult sometimes to differentiate between these two entities. However, the failure to distinguish the two, this article argues, will mythologize the life of the Prophet and then finally sacralize him. Therefore, this article proposes that the understanding of the sirah nabawiyah is the key in demythologization of the life of the Prophet